Inhibition and attentional control in pedophilic child sexual offenders – An event-related potential study. Issue 9 (September 2018) - Rosburg, Timm; Deuring, Gunnar; Boillat, Coralie; Lemoine, Patrick; Falkenstein, Michael; Graf, Marc; Mager, Ralph
Highlights: The study investigated action monitoring in pedophilic sex offenders by event-related potentials. The error positivity (Pe) amplitude was selectively diminished in offenders. Error evaluation processes appear to be impaired in pedophilic sex offenders. Abstract: Objective: Impaired response inhibition might play a role in child sexual offences. Recording of event-related potentials (ERPs) can help to clarify whether child sexual offenders (CSOs) show an altered processing of stop signals and commission errors. Methods: In the current ERP study, we investigated these processes in a Go/Nogo task on two groups of CSOs, pedophilic contact CSOs and non-contact CSOs (child pornography offenders), as well as on non-offenders as controls. Results: Behaviorally, CSOs showed a slight, but non-significant increase of the false alarm rate to Nogo cues, as compared to controls. The amplitudes of the ERP components N2 and P3 to Nogo cues followed by correctly withhold responses did not vary between CSOs and controls. The analysis of the ERPs to committed errors showed that the Ne amplitudes (reflecting error detection) did not differ between the groups either, whereas the Pe amplitudes (reflecting error evaluation and error awareness) were strongly diminished in CSOs. This diminishment was primarily found in contact CSOs. Conclusions: The findings suggest that response inhibition, processing of stop signals, and error detection are not necessarily impaired in CSOs. However, CSOs appear to dedicate less cognitive resources to the evaluation of committed errors. Significance: This selective alteration could reflect a reduced sense of responsibility for misconduct in this offender group, which might contribute to their delinquent behavior.